2014
DOI: 10.1371/journal.pone.0114743
|View full text |Cite|
|
Sign up to set email alerts
|

The Early Origin of the Antarctic Marine Fauna and Its Evolutionary Implications

Abstract: The extensive Late Cretaceous – Early Paleogene sedimentary succession of Seymour Island, N.E. Antarctic Peninsula offers an unparalleled opportunity to examine the evolutionary origins of a modern polar marine fauna. Some 38 modern Southern Ocean molluscan genera (26 gastropods and 12 bivalves), representing approximately 18% of the total modern benthic molluscan fauna, can now be traced back through at least part of this sequence. As noted elsewhere in the world, the balance of the molluscan fauna changes sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 99 publications
1
53
0
Order By: Relevance
“…More numerous and intense interspecific interactions are apparent from an increased proportion of predatory gastropods at two of the studied sites (Fig. 3E) and elsewhere (21,28,29) and a global diversity increase of marine metazoan predators in the wake of the mass extinction (3). Antipredatory behavior is also evident as an escape strategy in motile organisms and as an avoidance strategy in those that burrowed into the sediment, whereas morphological adaptations showed little effects at the KPB (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More numerous and intense interspecific interactions are apparent from an increased proportion of predatory gastropods at two of the studied sites (Fig. 3E) and elsewhere (21,28,29) and a global diversity increase of marine metazoan predators in the wake of the mass extinction (3). Antipredatory behavior is also evident as an escape strategy in motile organisms and as an avoidance strategy in those that burrowed into the sediment, whereas morphological adaptations showed little effects at the KPB (52).…”
Section: Discussionmentioning
confidence: 99%
“…Increased predation pressure after the KPB has been inferred from the radiation of predatory carnivores, in particular neogastopods (3,18,21,(26)(27)(28), elevated gastropod drilling frequencies (29,30), and a trend toward deeper burrowing in bivalves (31), but predatory Significance Global change and regime shifts of ecosystems are a major concern today. It has been suggested that the end-Cretaceous impact of an asteroid not only caused mass extinction but also involved the transgression of a global tipping point.…”
mentioning
confidence: 99%
“…None of the eight Late Maastrichtian species can be referred to extant genera, and only one of them crosses the K-Pg boundary. Both the increases in numbers of species and the proportion of modern genera up section are statistically significant (Crame et al, 2014). 3).…”
Section: Evolutionary Dynamics Of the Neogastropodamentioning
confidence: 95%
“…The Antarctic and two tropical localities all show clear indications that the richness of Early Cenozoic neogastropods peaked during the Middle Eocene (Crame et al, 2014;Dockery & Lozouet, 2003;Huyghe, Lartaud, Emmanuel, Merle, & Renard, 2015; Supporting Information Figures S1-S3). Nevertheless, levels of dissimilarity between all three localities in the Palaeocene are already extremely high, as there are no genera in common between the Paris Basin (42 genera) and Antarctica (19 genera), and only one between the U.S. Gulf Coast (45 genera) and Antarctica (Table 1; Appendix).…”
Section: A Quantitative Comparison Of Tropical and Polar Faunasmentioning
confidence: 99%
See 1 more Smart Citation